2013
DOI: 10.1063/1.4812037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of size and density differences on mixing of binary mixtures of particles

Abstract: Abstract. Mixing of granular materials is an important operation in many industries such as the pharmaceutical industry. Generally, a granular material to be mixed can have particles of different densities and sizes, which makes the mixing difficult. Several studies have addressed the issue of finding the optimum combinations of the size and density ratios of binary particles for mixing to happen, using rotating drums as the mixers. For mixtures of particles uniform in either the size or density, we have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…From the loading plot, it can be observed that PC2 is related with mixed information of APIs (high positive values) and formulation diluents (high negative values). An increase in the difference of powder density possibly leads to a high rate of segregation, caused by the generation of vertical driving force on the particles depending on the powder mixing [37]. This could be one of the possible causes for the segregation between APIs and diluents.…”
Section: Chemical Distribution and Internal Chemical Structurementioning
confidence: 95%
“…From the loading plot, it can be observed that PC2 is related with mixed information of APIs (high positive values) and formulation diluents (high negative values). An increase in the difference of powder density possibly leads to a high rate of segregation, caused by the generation of vertical driving force on the particles depending on the powder mixing [37]. This could be one of the possible causes for the segregation between APIs and diluents.…”
Section: Chemical Distribution and Internal Chemical Structurementioning
confidence: 95%
“…This becomes more important when the component under investigation is a minor one, and it is the case here for the EP granules. To have a reliable judgment about the mixture quality, the CoV of a randomly mixed system is also calculated using Equation (5). The standard deviation for this case is calculated from Equation (6) [49,53], P P…”
Section: Segregation Indexmentioning
confidence: 99%
“…There are various ways of controlling the segregation, including applying modifications to equipment geometry, changing the process operating conditions, balancing the effects of particles size and density, and/or manipulating their surface condition [4][5][6][7]. Focusing on the latter, it has a significant impact on inducing or reducing segregation mainly by influencing the flowability and mobility of particles [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mixer design depends on the nature of an industry, type of material, desired production rate, and the maximum acceptable variance in the product composition. This includes the mixer geometrical aspects, such as the blades/impellers shape and the mixer size as well as the operating mechanisms, namely the type of mixing (batch or continuous) and the power input per unit mass [1][2][3][4][5][6][7]. There are various types and models of mixers available which can be classified into two main categories of batch and continuous, each of which has its own advantages and disadvantages [8].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence and development of the DEM technique has paved the road towards designing more efficient and practical mixers. So far, the blending process in different types of mixers/blenders, namely the simple-rotating drums [18,19], tumbling blenders [20][21][22], bin blender [23], v-blenders [24][25][26][27], twin screw mixer [28], tote blenders [29,30], paddle mixers [31], double-cone blender [32], slant cone mixers [33,34], agitated tubular mixer [35], bladed mixers [5,7,17,36,37], and ribbon mixer [38], has been simulated using DEM. Continuous mixing is receiving more and more attention by pharmaceutical industries due to its advantages over the batch mixing.…”
Section: Introductionmentioning
confidence: 99%